2006
DOI: 10.1210/en.2005-1526
|View full text |Cite
|
Sign up to set email alerts
|

Global Profiles of Gene Expression Induced by Adrenocorticotropin in Y1 Mouse Adrenal Cells

Abstract: ACTH regulates the steroidogenic capacity, size, and structural integrity of the adrenal cortex through a series of actions involving changes in gene expression; however, only a limited number of ACTH-regulated genes have been identified, and these only partly account for the global effects of ACTH on the adrenal cortex. In this study, a National Institute on Aging 15K mouse cDNA microarray was used to identify genome-wide changes in gene expression after treatment of Y1 mouse adrenocortical cells with ACTH. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
42
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 74 publications
7
42
1
Order By: Relevance
“…The Zymogen Activation of PC5A Is Induced by ACTH-It was previously shown that PC5A mRNA is up-regulated in Y1 cells treated with ACTH or cAMP and that the mRNA levels of other PCs are not modulated by ACTH (34,35). In order to confirm and extend these data to the protein level, the cell surface localization of PC5A in Y1 cells was tested before and after 16-h treatment with either 8-Br-cAMP (Fig.…”
Section: A-c)mentioning
confidence: 81%
See 1 more Smart Citation
“…The Zymogen Activation of PC5A Is Induced by ACTH-It was previously shown that PC5A mRNA is up-regulated in Y1 cells treated with ACTH or cAMP and that the mRNA levels of other PCs are not modulated by ACTH (34,35). In order to confirm and extend these data to the protein level, the cell surface localization of PC5A in Y1 cells was tested before and after 16-h treatment with either 8-Br-cAMP (Fig.…”
Section: A-c)mentioning
confidence: 81%
“…It has been reported that furin, PACE4, and PC5A can process pro-ADAMTS-4, resulting in its activation (40). ADAMTS-4 mRNAs are highly up-regulated upon ACTH or cAMP treatments of Y1 cells (35). Therefore, it represented a logical substrate to analyze in our system.…”
Section: A-c)mentioning
confidence: 99%
“…Several high-throughput gene expression-profiling studies in the adrenal gland have been reported for human fetal and adult adrenal glands (42), adrenocortical tumors (20), normal subjects and patients with ACTH-dependent and -independent macronodular adrenal hyperplasia (9), steroidogenic enzymes in aldosterone-producing adenoma or cortisol-producing adenoma (3), human sporadic adrenocortical tumors (12), adrenocortical adenomas and carcinomas (52), primary pigmented nodular adrenocortical disease samples (24), and ACTH-induced gene expression in Y1 mouse adrenocortical cells (47). However, no study has focused specifically on transcription regulators that can be involved in both normal and abnormal adrenal physiology.…”
mentioning
confidence: 99%
“…Regulation of these factors was assessed at the gene or protein level either by adding ACTH to in vitro systems such as primary cell cultures from human, bovine, rat, and mouse adrenals, as well as the Y1 tumor adrenal cell line (10,23,27,28,30,31), or by removing ACTH in vivo through hypophysectomy of rats (16,18,29). The resulting effects demonstrate either the potential of ACTH to regulate a particular factor (in vitro experiments) or the reaction of intact adrenals to the sudden depletion of ACTH (in vivo experiments).…”
mentioning
confidence: 99%